(untitled) (Actual Problems of Mind, 2020)
This paper discusses the meaning of non-justificationism as an important part of Karl Popper’s philosophy of critical rationalism and William Bartley’s philosophy of pancritical rationalism. Сonstruals and attempted developments of critical rationalism by David Miller and Alan Musgrave are analysed and critically evaluated. The case is made that Miller’s rejection of the relevance of reasons for rationality runs counter to Popper’s view and is not supported by Popper’s and Bartley’s non-justificationist arguments. Besides, it is untenable because rationality cannot be reduced to the validity of arguments plus truth-value attributing «decisions» but essentially involves weighing up reasons for and against available options. With respect to Musgrave’s construal of non-justificationism and critical rationalism as the view that believing a proposition is rational if the proposition best survives critical scrutiny, it is argued that it is vulnerable to the problem of the infinite regress of criticizers (positions with which the scrutiny is to be carried out). The case is made that Popper’s-Bartley’s non-justificationism is to be understood as the identification of rationality with the openness to critical discussion in the search for truth and the claim that such discussion does not require ultimate unrevisable foundations, although it necessarily involves positions that are accepted for the purposes of the argument at hand without being provided with justification. In the perspective of critical rationalism, such positions play the role similar to that of «immediate knowledge» of classical rationalism and empiricism; however, unlike the latter, they are considered as fallible, open to examination, and revisable.